Design of Range Extend Multi-current Traction System Based on Energy Storage - Fengbing JIANG; Ying GAO; Bin ZHANG; Xueming LI; Yuyu XIONG (机车电传动)
In order to meet the application of multiple power supply systems and have the functions of battery traction, the range extend multi-current traction system based on battery energy storage was developed. The design idea of the traction system was expounded. The system design parameters, topology and main circuit and working principle of key components such as traction converter and bidirectional charger were introduced in detail. Some key technologies used in the system were analyzed and studied. The results of system combination test and loading show that the traction and braking characteristics of the traction system under different power supply systems and the charging and discharging performance of bidirectional charger all meet the design requirements.